Engineering redox metabolism in yeast - Vitay, Dóra (My University, 2017)
Saccharomyces cerevisiae is a widely used model organism in metabolic engineering as it is also one of the most used microorganisms in the fermentation industry. It is used for producing a vast variety of chemicals, mainly ethanol. Fatty acids are one of the chemicals for potential industrial scale production with yeast, due to their usage in multiple industries, such as food or cosmetics industry. The production of fatty acids in yeast is a well-studied phenomenon and many strategies to improve its production in yeast have been attempted, for example increasing the precursor metabolite acetyl-CoA and deleting competing metabolic pathways. Fewer studies have investigated if fatty acid overproducing strains are limited by NADPH availability – a cofactor required in large quantities during fatty acid biosynthesis. Therefore, this study investigates a possible way to overcome the elevated NADPH need of a fatty acid producing S. cerevisiae strain via modulating the regulation of transcription factor Stb5. Stb5 regulates most genes in the pentose phosphate pathway, which is an important source of NADPH in yeast. Moderate overexpression of STB5 should push the carbon flux through the oxidative pentose phosphate pathway and therefore provide a larger pool of NADPH for the cell. In addition, the downregulation of the glycolytic gene TPI1 could also reroute the flux from glycolysis to the pentose phosphate pathway. In this study, we show two possible methods for modulating the expression of these two target genes and their effect on the NADPH levels and free fatty acid production: modulation via the pCUP1 copper inducible promoter and via constitutive promoters of different strength.
Keywords: Biokemi och molekylärbiologi; Mikrobiologi; Annan industriell bioteknik; Livsvetenskaper; Biochemistry and Molecular Biology; Microbiology; Other Industrial Biotechnology; Life Science